Length of stay in rehabilitation influences magnitude of the acute stress response in birds of prey - Klingbeil, Naomi; Nuzzo, Jacques T.; Seitz, D. Jane; Chan, Beth; Wilcoxen, Travis E. (Wildlife Rehabilitation Bulletin, 2024)
Wild animals are occasionally injured or become ill as a result of natural causes or human activity. As a way to remediate the damage imposed by humans on wildlife populations, these animals may be taken in for rehabilitation. Federal laws for rehabilitators set limits for the length of time a bird can remain in rehabilitation before a final decision on release or euthanasia is made. Little is known about the consequences of longer stays in captivity within that limited window with regard to stress physiology of the animals. The authors hypothesised that length of stay in rehabilitation would influence the ability of raptors to mount a full stress response upon release from rehabilitation. Blood samples were taken from each bird upon admission for rehabilitation and immediately prior to their release, a process by which the animals are exposed to a significant, acute stressor of capture, handling, and examination. A blood sample was collected for analysis of heterophil to lymphocyte ratios (H:L), which are indicative of long-term baseline stress. The authors found that as length of stay increased, the difference in corticosterone levels reached during an acute stressor from admission samples to release samples decreased. Baseline stress, as indicated by H:L, was not significantly affected by length of stay. The results suggest that birds of prey in rehabilitation habituate to captivity the longer they stay in captivity and may lose some degree of natural responsiveness to stressors.